(untitled) (Bangladesh Journal of Neurosurgery, 2024)
Background: Cervical myelopathy is a common cause for neurosurgical outpatient department visit, and a substantial proportion of patient suffering from myelopathy due to cervical spondylosis has to go through surgical management, commonly anterior cervical decompression and fusion in the form of Cloward’s procedure, Smith Robinson procedure, PEEK and Titanium cage implant and fusion. A total of 23 cases were selected according to predefined inclusion and exclusion criteria. Method: This is a prospective study that was conducted in the Department of Neurosurgery, Bangabandhu Sheikh Mujib Medical University. Patients with cervical myelopathy undergoing anterior cervical decompression and fusion, in the form of Cloward’s procedure, Smith Robinson procedure, or Anterior Cervical Discectomy with Poly Ether Ether Ketone (PEEK) and Titanium cage implants in a single level for inclusion and exclusion criteria. Results: This study found out that the Modified Nurick grading system is a useful tool to quantify the functional status of the patients suffering from cervical myelopathy and surgery in various forms of anterior cervical decompression and fusion has an impact on the functional status even at an early period of one month. 82.6% of the patients had functional improvement, whereas 13% remained the same. Only one out of the 23 patients deteriorated. Various methods of anterior cervical decompression and fusion or the levels of involvement did not have any statistically significant impact on improvement among the patients. Conclusion: Anterior cervical decompression and fusion is a time-proven treatment modality for the patients suffering from cervical myelopathy owed to external compression due to spondylotic changes and Ossified Posterior Longitudinal Ligament. The functional status of the patients that have been compromised due to the disease shows promising change even in the early period undergoing surgery. Bang. J Neurosurgery 2023; 13(1): 3-9